2024
DOI: 10.1002/anie.202313640
|View full text |Cite
|
Sign up to set email alerts
|

L‐Glycosidase‐Cleavable Natural Glycans Facilitate the Chemical Synthesis of Correctly Folded Disulfide‐Bonded D‐Proteins

Weiwei Shi,
Tongyue Wang,
Ziyi Yang
et al.

Abstract: D‐peptide ligands can be screened for therapeutic potency and enzymatic stability using synthetic mirror‐image proteins (D‐proteins), but efficient acquisition of these D‐proteins can be hampered by the need to accomplish their in vitro folding, which often requires the formation of correctly linked disulfide bonds. Here, we report the finding that temporary installation of natural O‐linked‐β‐N‐acetyl‐D‐glucosamine (O‐GlcNAc) groups onto selected D‐serine or D‐threonine residues of the synthetic disulfide‐bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…129 Additionally, a recent study demonstrated that modification with O-GlcNAc, which can be cleaved by Lglycosidase enzymes, facilitates the chemical synthesis of correctly folded D-proteins including mirror-image tumor necrosis factor alpha (D-TNFα) and mirror-image receptorbinding domain of the Omicron spike protein (D-RBD). 130 The methods of temporary structural support to promote protein ligation and folding, along with other tools such as isoacyl dipeptides 135−137 and removable solubilizing tags, 138−146 have expanded the capabilities of chemical protein synthesis, providing effective approaches for synthesizing increasingly challenging and larger protein targets. These advancements make it more effective to synthesize midsized human proteoforms with lengths of 300−500 amino acids, including those with poor water solubility (e.g., membrane proteins).…”
Section: Human Proteoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…129 Additionally, a recent study demonstrated that modification with O-GlcNAc, which can be cleaved by Lglycosidase enzymes, facilitates the chemical synthesis of correctly folded D-proteins including mirror-image tumor necrosis factor alpha (D-TNFα) and mirror-image receptorbinding domain of the Omicron spike protein (D-RBD). 130 The methods of temporary structural support to promote protein ligation and folding, along with other tools such as isoacyl dipeptides 135−137 and removable solubilizing tags, 138−146 have expanded the capabilities of chemical protein synthesis, providing effective approaches for synthesizing increasingly challenging and larger protein targets. These advancements make it more effective to synthesize midsized human proteoforms with lengths of 300−500 amino acids, including those with poor water solubility (e.g., membrane proteins).…”
Section: Human Proteoformsmentioning
confidence: 99%
“…The basic idea behind the temporary support strategy can be compared to building a house or bridge in the macroscopic world, where temporary structural scaffolding is often strategically used to ensure the stability of the building at intermediate stages before the entire structure is completed (Figure a). By mimicking this idea and leveraging the remarkable tolerance of the peptide hydrazide ligation strategy to various chemical functionalities, we have developed several families of customized removable auxiliary groups as temporary structural supports and installed them onto synthetic protein intermediates to improve their ligation and folding behaviors. …”
Section: Chemistry Needed For the Synthesis Of Human Proteoformsmentioning
confidence: 99%
See 1 more Smart Citation